Proceedings of the 40th International Academic Conference, Stockholm 2018
DOI: 10.20472/iac.2018.040.044
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Large Classes at an Institution of Higher Learning in South Africa

Abstract: In line with the notions of increased access to education as well as massification of education in South Africa and elsewhere, large classes have become common in Universities. While the size of a large class varies from country to country, in a South African context, and at our institution in particular, large classes can mean approximately 120 students in one seating. Although large classes can have a negative effect on student participation and engagement, especially when dealing with first year students, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…This is because, in a large class setting, learning is lecture centred, often resorting to traditional forms of teaching and learning, with minimal student engagement. The poor engagement and performance of students are exacerbated by the fact that, in many large class settings, students are usually heterogeneous in terms of language and aptitude, making it difficult for those who cannot express their opinions and raise their concerns in class (Maringe, 2020) This argument is further supported by a study conducted by (Matoti et al, 2018), which found that 60% of the students who participated in their study reported that the presence of many people in class deterred them from asking questions.…”
Section: Teaching Large Classesmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because, in a large class setting, learning is lecture centred, often resorting to traditional forms of teaching and learning, with minimal student engagement. The poor engagement and performance of students are exacerbated by the fact that, in many large class settings, students are usually heterogeneous in terms of language and aptitude, making it difficult for those who cannot express their opinions and raise their concerns in class (Maringe, 2020) This argument is further supported by a study conducted by (Matoti et al, 2018), which found that 60% of the students who participated in their study reported that the presence of many people in class deterred them from asking questions.…”
Section: Teaching Large Classesmentioning
confidence: 99%
“…Hence, this transition process left many academics and students behind. For students, online learning had its own challenges like (a) a sense of isolation due to lack of interaction between peers (Moore, 2020); (b) difficulties with hands-on learning activities (Matoti et al, 2018); (c) academics' limited presence (Maringe, 2020); and (d) timely support (Trust & Whalen, 2020). A sudden move from traditional face to face learning to online resulted in a big shock to academics and students, regardless of whether these stakeholders were ready for it or not.…”
Section: Teaching Large Classesmentioning
confidence: 99%
See 1 more Smart Citation
“…Much attention was given to the preparedness of lectures to teach academic writing skills and how well students are prepared for academic writing tasks. Another huge challenge is the overcrowded classes and small venues makes it difficult for lecturers, especially the Education programme to teach and assess academic writing skills (Matoti & Lenong, 2018). The findings of Boughey and McKenna (2016) suggested that it has become obvious that the way in which academic literacies expected of students in academic contexts is viewed by some students as colonial and writing 'skills' out the belief that it was needed by students to succeed in the academy (Pineteh, 2014.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Indonesia also deals with the same issue regarding the size of university classes, where there are commonly more than 30 students (Hadi & Arante, 2015). As a consequence, large classes have become an issue that is of great concern for many researchers who have investigated this topic in different countries such as China, Africa, France, and Vietnam, with a particular focus on the context of English as a foreign language (EFL) teaching and learning (Matoti & Lenong, 2019;Mulryan-Kyne, 2010;Shan, 2020;Thi & Anh, 2019). While, in Indonesian EFL context, the topic of large classes has not been much explored, and most importantly, how teachers handle them is scarcely discussed.…”
Section: Introductionmentioning
confidence: 99%